Manufacturing of Silage Feed for Daily Goats in Lama Vilage, Pancur Batu District - Br. Ketaren, Nurjama'yah; Lindawati; Siregar, Etti Sartina (Talenta Publisher, 2023)
Giving quality feed to dairy goats can increase milk production. In the rainy season, the availability of grass and forage is abundant, while in the dry season the availability of local feed is reduced. Forage preservation technology and other local feeds are needed to be available continuously. This can be overcome by applying the manufacture of silage feed using fermentation technology. The method applied in this service activity is the transfer of knowledge conveyed in the socialization activity in the form of 1) introduction of agricultural and agro-industrial waste that can be used as an alternative forage and concentrates, (2) preparation of formulated dairy goat feed, (3) silage feed manufacturing technology and (4) monitoring and mentoring activities. The socialization ware carried out in the form of a lecture followed by a question and answer session. The results of the activities of farmers know some local feeds that have the potential to be used as animal feed, know how to make feed formulations and technology for making silage feed. The knowledge and skills of making silage feed that has been owned by farmers are expected to overcome the difficulties of farmers in sustainably providing feed and can increase goat milk production.